Geography and rural development - Sinha, R.N.P.; Sinha, Ram Nandan P. (Ram Nandan Prasad), 1932- (New Delhi : Concept Pub., 1992)
With reference to India; symposium papers.
Includes index.
Keywords: Rural development -- India -- Congresses; Geography -- India -- Congresses; Regional planning -- India -- Congresses; Land use, Rural -- India -- Congresses; India -- Rural conditions -- Congresses; India -- Economic conditions -- Congresses